Linguistic approaches in film-theory: a movement against film language - D. A. Polikarpova (Дискурс)
Introduction. The correctness of “film language” concept as the most common designation of specific cinematographic techniques is questioned since it caused the formation of typical audience responses to a film.Materials and methods. The work proposes to define three basic meanings of the “film language” concept and trace their formation on the basis of classical and modern film theory.Results. The main approaches of the film theory focus on an analogies search between cinema and language (linguistic, semiotic). The example of their basic assertions criticism on the basis of a modern Anglo-American film philosophy is given, thus resulting in the conclusion of their theoretical inadequacy.Discussion. Possible directions of film theory movement beyond language analogies are outlined. It is proposed to note the film techniques that in principle do not have the designation function. An example of the minimum cinematic elements related to the audio-visual field of the cinema itself is provided. The thesis on changing the typical audience viewing responses from an interpretive “understanding” to a sensual “encounter” is proposed for further discussion.Conclusion. It is necessary to continue the theoretical work which refuses linguistic analogies and interpretive position of theorist and viewer and makes movement towards a conversation on the autonomous existence mode of cinematography possible.